2014
DOI: 10.1186/1471-2164-15-387
|View full text |Cite
|
Sign up to set email alerts
|

Finished sequence and assembly of the DUF1220-rich 1q21 region using a haploid human genome

Abstract: BackgroundAlthough the reference human genome sequence was declared finished in 2003, some regions of the genome remain incomplete due to their complex architecture. One such region, 1q21.1-q21.2, is of increasing interest due to its relevance to human disease and evolution. Elucidation of the exact variants behind these associations has been hampered by the repetitive nature of the region and its incomplete assembly. This region also contains 238 of the 270 human DUF1220 protein domains, which are implicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 28 publications
1
67
0
Order By: Relevance
“…In the present contribution, we use a genome mapping system 1,2,23 to make massively parallel measurements of DNA extension at the single-molecule level on barcoded DNA molecules. The approach begins with sheared, labeled genomic DNA from E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…In the present contribution, we use a genome mapping system 1,2,23 to make massively parallel measurements of DNA extension at the single-molecule level on barcoded DNA molecules. The approach begins with sheared, labeled genomic DNA from E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…mCNV breakpoints frequently are flanked by high-identity repetitive sequence, further limiting imputation and association of this form of genetic variation with human phenotypes. Haplotyperesolved sequencing of these regions has consistently shown that such inferential genotyping underestimates the genetic complexity of the underlying genetic variation of these regions (Boettger et al 2012;Steinberg et al 2012;Antonacci et al 2014;O'Bleness et al 2014). Several lines of evidence suggest that this missing variation will be critical to interpreting the "missing heritability" of human disease.…”
mentioning
confidence: 99%
“…In primates, this ancestral domain has been duplicated many times over, reaching its peak abundance in humans where several hundred DUF1220 domains exist across 20-30 genes in the Nuclear Blastoma Breakpoint Family (NBPF) (Vandepoele et al 2005;Dumas et al 2012). The majority of these map to 1q21.1, a chromosomal region with complex, and unstable genomic architecture (O'Bleness et al 2012(O'Bleness et al , 2014.…”
Section: Introductionmentioning
confidence: 99%